Evaluating the Performance of Modified Watershed Algorithm Based on DBMF and DT. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
The image segmentation; segments a given image into separate regions and objects. It is widely used in various vision applications like face detections, motion detection etc. It has been found that the noise has affected the segmentation at a great extent; so to overcome this problem we have presented a modified watershed segmentation using Decision based median filtering (DBMF) and Dynamic thresholding (DT). DBMF has the ability to reduce the high density of noise in the image so will provide more efficient results. However DT has also refined segmentation process further. The comparisons have shown that the proposed algorithm provides quite significant results over the available methods.